Pharmacological and biochemical modulation of stress markers by L-NAME and L-Ascorbic acid in chronic restraint model in Wistar rats - Pal, Giridhari; Rohil, Vishwajeet; Akhtar, Razi; Behl, Tapan; Bharati, Sudha; Swain, Trupti Rekha; Imran, Mohammed; Jena, Jyotirmoyee (Asian Journal of Medical Sciences, 2017)
Background: Stress is the psycho-physiologic reaction of the body to diverse stimuli including emotional or physical stimuli that imbalance the homeostasis and is also known to trigger various stress markers. Despite the stressors of different types, chronic stress in particular, is known to influence the physiological milieu and breakdown of adaptive mechanisms consequently aggravating the morbid states. Aims and Objectives: The present study was designed to evaluate the modulatory role of stress marker by N-nitro-L-arginine-methyl ester (L-NAME) and L-Ascorbic acid (L-AA) in experimental model of chronic restraint stress (RSx21) in Wistar rats. Materials and Methods: MDA and GSH levels were determined by the method of Okhawa et al 1979 and Ellman 1959 respectively, the SOD and catalase levels were estimated by the method of Nandi and Chatterjee 1988 and Aebi 1984 respectively. Results: Results from our study reveal the significant enhancement of malondialdehyde (MDA) level while significant attenuation of superoxide dismutase (SOD), reduced glutathione (GSH) and catalase levels in chronic stress group compared with vehicle (non-stress) group. The MDA level was found to be increased by L-NAME (10 and 50 mg/kg) in chronic restraint (RSx21) induced rats as compared to vehicle treated RS group. Antioxidant L-AA (100 and 200 mg/kg) significantly reduced MDA level in chronic stress situation. However, L-NAME and L-Ascorbic Acid were found to cause an increase in level of plasma SOD, GSH and catalase when compared with vehicle treated RS group. On the other hand, L-AA (100 and 200 mg/kg) reversed these RS induced changes in these oxidative parameters. Conclusions: Hence, results from the study underlined the intricate role of antioxidants as evidenced by reversal of oxidative stress markers that command a vital role in the development of morbid condition. Asian Journal of Medical Sciences Vol.8(1) 2017 15-20